?COMPARATIVE ELEMENTAL CONTENTS (Cu, Ca, Zn, K, Mg, Ni, Fe AND Cd) OF SEVEN VARIOUS EDIBLE TUBERS IN NIGERIA - BAMIRO, F.O.; ESUOSO, K.O.; TAIRU, O.A. (Biological Sciences - PJSIR, 1995)
. Seven different types of popular tubers consumed in Nigeria have been analysed for their elemental cornposi- non. Metals that were investigated include Ca, Cu, Zn, K, Mg, Na, Ni, Fe, and Cd. Results obtained showed that samples contain high amount of potassium and sodium; moderately low amount of magnesium and calcium while zinc, iron, nickel and cadmium were present at trace levels. Amount of zinc in most samples was found to be about 34 times higher than the amount of cadmium. This was found to be an advantage in masking Cd-induced hyperten- sion In some mammals.· .